Reversible data hiding scheme based on 3-Least significant bits and mix column transform - Abduallah, Wafaa Mustafa; Rahma, Abdul Monem S.; Pathan, Al-Sakib Khan (2013)
Steganography is the science of hiding a message signal in a host signal, without any perceptual distortion of the host signal. Using steganography, information can be hidden in the carrier items such as images, videos, sounds files, text files, while performing data transmission. In image steganography field, it is a major concern of the researchers how to improve the capacity of hidden data into host image without causing any statistically significant modification. In this work, we propose a reversible steganography scheme which can hide large amount of information without affecting the imperceptibility aspect of the stego-image and at the same time, it increases the security level of the system through using different method for embedding based on distinct type of transform, called Mix Column Transform. Our experimental results prove the ability of our proposed scheme in balancing among the three critical properties: capacity, security, and imperceptibility.